Good radiological and functional results after intramedullary nailing of distal radius fractures. Issue 4 (September 2013) - Dremstrup, Lene; Skjærbæk, Mette S.; Olesen, Steen; Høgh, Anette; Hansen, Torben B.
Abstract To evaluate the results after fixation of distal radius fractures using Micronail® internal fixation, a prospective cohort study was performed, including displaced fractures of the distal radius (AO type A 2.2, A3.1, and A3.2). In total, 60 patients were included and 44 patients were available for 1-year follow-up (radiological and clinical examination) and 39 for 5-year follow-up (telephone interview). It was found that all fractures healed, with an average radial volar tilt of 2°, radial length of 11 mm, and a radial inclination of 22°. The functional result was excellent-to-good in 93% of the patients. Thirteen patients (30%) reported paraesthesia of the superficial branch of the radial nerve at the 1-year follow-up. In four patients the paraesthesia of the radial nerve was persistent. No other complications or reoperations were reported by the patients at the 5-year follow-up and only one implant had been removed. The study confirms that the Micronail® is a minimal invasive method that can provide a stable fixation of selected distal radius fractures and provide a good functional outcome with a very low need of implant removal after fracture healing with few complications related to the operation, the main complication being permanent damage to the radial nerve.